Hazard Analysis Critical Control Point (HACCP) Education Shredded Catfish Products at UMKM XYZ - Safrina Salsabila; Caezario Budi Kurniawan; Riski Ayu Anggreini; Diana Aqidatun Nisa; Nurul Widji T. (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Catfish is the result of freshwater aquaculture which is often found in Mojokerto Regency, East Java. XYZ Micro, Small and Medium Enterprises (UMKM) is a business engaged in the processing of catfish, with shredded catfish as one of its products. Hazard Analysis Critical Control Point (HACCP) is one of the factors that influence the quality of food products, but XYZ SMEs do not understand this. One of the efforts that can be made for the XYZ MSME business in improving its products is by conducting HACCP-related education. The form of activities carried out in this activity is identifying hazards during the production process, which includes observation, analysis and determination of critical points, giving advice, and implementing control measures. The results of these activities were that UMKM XYZ was able to improve the quality of catfish shredded production. This is evidenced by the creation of SOPs at each stage of catfish shredded production. The application of HACCP is expected to improve the quality and safety of catfish shredded products.